Perancangan Ulang Interior Sekolah Tinggi Kesehatan Indonesia Wirautama Ciparay Dengan Pendekatan Aktivitas - Aufa, Ezra; Akhmadi; Haristianti, Vika (Telkom University, 2024)
The need for healthcare services in Indonesia is crucial and a top priority for improving the quality of life of its citizens. The quality of healthcare services largely depends on nurses, who constitute the majority of healthcare workers in Indonesia. STIKes Indonesia Wirautama Ciparay, as the only higher education institution in the field of health in Ciparay, is committed to producing professional healthcare personnel. With the increasing number of students, a second campus was established in 2022. However, this new building lacks adequate facilities, such as practical laboratories and classrooms that do not meet national standards. This study aims to redesign the interior of the new building of STIKes Indonesia Wirautama Ciparay using an activity-based approach to create a comfortable and supportive learning environment. This approach focuses not only on creating physical comfort in the rooms but also on providing facilities that support the teaching and learning process. Thus, it is expected to create a more focused and comfortable learning environment, helping to improve the quality of education and produce competent and professional healthcare personnel. Keywords: redesign, nurses, STIKes Indonesia Wirautama Ciparay, activities.